GAME TECHNOLOGIES IN THE RUSSIAN LANGUAGE LESSONS AS ONE OF THE WAYS TO ENHANCE THE COGNITIVE ACTIVITY OF STUDENTS IN GRADES 5–9 - Rano Utanova Jabbarovna; Shakhida Karasakalova Abdikarimovna (American Journals, 2012)
This article provides information on the importance and benefits of using game technologies in Russian language lessons.